تأثير الرقص الشعبي بأسلوب العروض الرياضية على بعض عوامل القدرات الابداعية الحركية لتلاميذ الحلقة الثانية - ابراهيم, قاسم; علي, محمد; الطواشي, سلام (Latakia University Journal -Medical Sciences Series, 2018)
ان أهمية الابداع الحركي في المجال الرياضي تتجلى في الدور الذي يلعبه الابداع في الارتقاء بالذكاء الحركي وانتاج لأكبر عدد ممكن من الأفكار والحركات غير الشائعة والتقليدية وايجاد الحلول للمشاكل, وعليه هدفت هذه الدراسة إلى التعرف على تأثير الرقص الشعبي بأسلوب العروض الرياضية على بعض عوامل القدرات الابداعية الحركية(الطلاقة الحركية, المرونة الحركية, الأصالة الحركية) لتلاميذ الحلقة الثانية في محافظة حماه, وقد استخدم الباحث المنهج التجريبي بتصميم المجموعة التجريبية الواحدة كونه المنهج الذي يتناسب مع طبيعة البحث ومشكلته والمقارنة بين القياسين (القبلي_البعدي), وقد بلغ حجم العينة(20)تلميذ وتلميذة من تلاميذ الصف السادس موزعة بالتساوي (10) تلميذات و(10) تلاميذ تستخدم برنامج الرقص الشعبي بأسلوب العروض الرياضية لمدة8 أسابيع بواقع وحدتين اسبوعيا, وأشارت النتائج التي تم التوصل اليها الى فاعلية برنامج الرقص الشعبي بتنمية بعض عوامل القدرات الابداعية الحركية (الطلاقة الحركية, المرونة الحركية, الأصالة الحركية ) لدى تلاميذ الحلقة الثانية. The importance of the motor creativity in the field of sports is reflected in the role played by creativity in the development of the motor intelligence and the production of as many as possible ideas and movements are not common and traditional solutions to find problems, the aim of this study was to identify the effect of folk dance in the style of sports performances on some of the creative and motional abilitie (motional fluency, motional flexibility, motional originality) on the student of the second seminar in Hama governorate, The researcher used the experimental method as the method that is appropriate to the nature of the research and its problem, has been chosen as one of its designs with preceding and dimensional measurement, of the (20) students and sixth graders divided equally(10) students and (10) students using the program of folk dance in the style of sports performances, . The results showed the effectiveness of folk dance in the style of sports performances of in the development of some factors of the creative and motion abilities(motor fluency, motor flexibility, motor originality) on the student of the second seminar